War of Necessity : War of Choice : A Memoir of Two Iraq Wars - Haass, Richard N. (New York Simon & Schuster, 2009)
Richard Haass--a member of the National Security Council staff for the first President Bush and the director of policy planning in the State Department for Bush II--contrasts the decisions that shaped the conduct of the two Iraq wars and makes a crucial distinction between the 1991 and 2003 conflicts, while offering an examination of the means and ends of U.S. foreign policy: how it should be made, what it should seek to accomplish, and how it should be pursued.
Include Appendix, Note and Index
Keywords: Military policy -- Persian Gulf War (1991) -- United States -- Middle East -- Iraq War (2003-2011)